Effect of corporate social responsibility on corporate image of commercial government-owned entities in Kenya - Kung’u, Victor Wainaina (Strathmore University, 2021)
Despite corporate social responsibility being a noble objective, it is only secondary to such organisations because there are other pressing concerns, profit-seeking activities that are more closely linked with the core business. As such most organizations have overlooked the role, corporate social responsibility can have on the organization. More so, in the current environment, most state-owned commercial entities in Kenya are engulfed in fraud, lossmaking and poor service delivery, as well as endemic corruption, which has negatively affected the public perception of the institution. Thus, it was critical to analyse, if any, the influence corporate social responsibility may have on the corporate image of the organization. Specifically, the study focussed on the effect of economic, environmental, ethical and legal social responsibility on the corporate image. Theoretically, the study relied on Stakeholder Theory and Corporate Social Performance Theory. The research utilized a positivism paradigm in the examination of the study problem. A quantitative approach was predominantly applied in the study. The unit of analysis for the current research was the 50 commercial and financial government-owned entities in Kenya. The study targeted three senior-level managers in each of the institutions leading to a sample frame of 150 respondents. The sample size was calculated using the Yamane formula, which leads to 109 participants being considered in the research. The study used non-probability sampling in the selection of study participants. The study employed a structured research questionnaire that was administered using physical questionnaires and electronic methods as deemed convenient. The research quality was fostered through reliability and validity tests that was conducted in a small sample of 10% (N=11) of the respondents. The collected data was analysed using SPSS 25, with descriptive and inferential tests being employed. The results were presented using bar graphs, charts and tables. The survey obtained a 67% response rate. The correlation tests indicated there was a strong positive effect of economic and environmental social responsibility on the corporate image. The study further affirmed there is a moderate and positive effect of ethical and legal social responsibility and corporate image of state corporations in Kenya. The regression analysis showed that 51% of the changes in the corporate image of state commercial corporations in Kenya are determined by corporate social responsibility in Kenya. The study concluded that economic and ethical social responsibility has a significant positive effect on corporate social responsibility. Also, it was concluded that environmental and legal social responsibility aspects have insignificant influence on the corporate image of firms. The study recommends that the national government should develop guidelines to guide the certification of corporate social responsibility efforts within commercial corporations. Further, it is recommended that commercial corporations should strengthen their implementation of social responsibility activities which will be vital to extending the corporate image of the firms.
A Thesis submitted in partial fulfillment of the requirement for the Degree of Master of Commerce at Strathmore University
Keywords: Corporate social responsibility; Corporate image; Commercial government-owned entities_Kenya